Judicial Justice in Polygamy Permits Based on Quraish Shihab’s Perspective - Achmad Aisyul Mazidi; Muhammad Faisol; Martoyo Martoyo (Academia Open, 2025)
General Background: Polygamy remains a controversial issue in Islamic family law and judicial practice in Indonesia, primarily centered on the requirement of justice as mandated in Surah An-Nisa verse 3. Specific Background: In practice, achieving fairness in polygamy often faces challenges, particularly in judicial decisions granting polygamy permits. Quraish Shihab’s interpretation of justice emphasizes balance and contextual fairness, offering a multidimensional perspective for analyzing such rulings. Knowledge Gap: Previous studies have not deeply examined how judges operationalize Quraish Shihab’s concept of justice in actual polygamy permit decisions. Aims: This study aims to analyze the application of justice principles in the Jember Religious Court’s Decision No. 1775/Pdt.G/2023/PA.Jr using Quraish Shihab’s justice framework. Results: The findings reveal that the judges’ considerations emphasize procedural and formal justice—such as equality before the law and compliance with legal requirements—while substantive justice, including psychological and social balance for wives and children, remains limited. Novelty: This study provides an integrative analysis linking Islamic theological concepts of justice with judicial reasoning in polygamy cases. Implications: The research highlights the need for a holistic judicial approach that not only fulfills legal formalities but also ensures equitable family welfare consistent with maqasid al-shariah principles. Highlights: Examines judicial justice in polygamy permit decisions. Applies Quraish Shihab’s concept of balanced fairness. Reveals dominance of formal over substantive justice. Keywords: Justice, Polygamy, Quraish Shihab, Religious Court, Islamic Law